2022
DOI: 10.1186/s12902-022-01013-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anxiety, depression and disease-related distress on long-term glycaemic variability among subjects with Type 1 diabetes mellitus

Abstract: Background Anxiety, depression, and disease-related distress are linked to worse overall glycaemic control, in terms of HbA1c. This study was aimed to evaluate whether traits of these emotional disorders are associated with long-term glycaemic variability in subjects with Type 1 diabetes. Methods Longitudinal retrospective study. Six-year HbA1c data (2014–2019) from 411 subjects with Type 1 diabetes who had participated in a previous study to desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Diabetes distress is increasingly considered one of the most important psychosocial issues in the care of people with T1D; therefore, an international consensus study recommended that the measurement of diabetes-related burden or stress should be a key clinical outcome measure in studies of emerging adults [ 7 ]. Diabetes distress in emerging adults is still an understudied phenomenon, even though it is common and occurs more frequently in this age- group and is suspected to contribute to adverse outcomes [ 2 ], such as higher haemoglobin A1c (HbA1c) levels [ 8 10 ], higher glycaemic variability [ 11 ], impaired quality of life [ 9 ], more severe depressive symptoms [ 8 ], and worse physical and mental health [ 8 , 9 ]. Since diabetes distress, depressive symptoms and HbA1c levels are interrelated, it seems appropriate to examine these factors simultaneously [ 6 , 8 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes distress is increasingly considered one of the most important psychosocial issues in the care of people with T1D; therefore, an international consensus study recommended that the measurement of diabetes-related burden or stress should be a key clinical outcome measure in studies of emerging adults [ 7 ]. Diabetes distress in emerging adults is still an understudied phenomenon, even though it is common and occurs more frequently in this age- group and is suspected to contribute to adverse outcomes [ 2 ], such as higher haemoglobin A1c (HbA1c) levels [ 8 10 ], higher glycaemic variability [ 11 ], impaired quality of life [ 9 ], more severe depressive symptoms [ 8 ], and worse physical and mental health [ 8 , 9 ]. Since diabetes distress, depressive symptoms and HbA1c levels are interrelated, it seems appropriate to examine these factors simultaneously [ 6 , 8 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adequate insulin production, insulin sensitivity, glucose intake, along with a variety of other endocrine factors (glucagon like peptide-1, glucagon) establish glycemic control and are related to diabetes severity [5]. Depression and anxiety have been examined across multiple diabetes subgroups including individuals with type 1 [6], type 2 [7], and gestational diabetes [8].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of diabetes type, anxiety and depression are associated with poorer glycemic control [6][7][8]. Overall, research indicates that mental and physical health are closely linked, particularly between hyperglycemia and depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological factors, especially disease-related stress, and anxiety, are associated with long-term glycemic variability in subjects with type 1 diabetes resulting in higher levels of oxidative stress and vascular and tissue damage than permanent hyperglycemia, and many observational studies with posthoc analyses of clinical trials have reported associations between glycemic variability and the development of micro-and macrovascular diabetic complications, severe and nocturnal hypoglycemia and overall mortality 24 .…”
Section: Nusantoro Ap Et Al/ 2018mentioning
confidence: 99%